THE EFFECTIVENESS OF A WEB-BASED, PREVENTION INTERVENTION ON HIGH-INTENSITY DRINKING BEHAVIORS, ATTITUDES, AND BELIEFS, AMONG FIRST-YEAR STUDENTS - Sharpe, Justin Lee Wesley (East Carolina University)
Harmful alcohol consumption among college-aged students remains a significant public health problem affecting institutions across the United States despite the implementation of various individual and environmental evidence-based solutions. Rising costs and the challenge of adapting interventions to meet the evolving needs of students and campus environments underscore the need to explore this topic further. This inquiry examines the effectiveness of a web-based, personalized feedback intervention designed in-house at the site of this inquiry. It aims to contribute to the existing research on evidence-informed solutions and their effects on alcohol-related behaviors, attitudes, and beliefs among incoming first-year students. An explanatory sequential mixed-methods research design was used to assess the influence of the web-based intervention on participants' behaviors, attitudes, and beliefs. Quantitative findings indicate a statistically significant increase in harm reduction strategy utilization following the implementation of the intervention and continued increase after arrival at The University. Qualitative data suggests an emphasis on the honest and practical approach to preventing substance misuse by focusing on harm reduction strategies rather than an abstinence-only approach without being overly persuasive or judgmental. Participants expressed appreciation of the harm reduction approach, emphasizing informed decision-making by utilizing the Personalized Feedback Report. This inquiry contributes to an existing body of literature by further highlighting web-based interventions and their role in mitigating alcohol misuse among college-aged students and offers a potential alternative for institutions.
Keywords: Alcohol Consumption; Underage Drinking; First-Year Students; College & University; Personalized Feedback Intervention; Web-based Intervention; Orientation; College freshmen--Alcohol use--United States--Prevention; College freshmen--United States--Attitudes; College freshmen--Health and hygiene--United States; Harm reduction